A review on proton exchange membrane multi-stack fuel cell systems: architecture, performance, and power management. (15th March 2022) - Zhou, Su; Fan, Lei; Zhang, Gang; Gao, Jianhua; Lu, Yanda; Zhao, Peng; Wen, Chaokai; Shi, Lin; Hu, Zhe
Highlights: The detailed advances in the multi-stack fuel cell system (MFCS) are reviewed. The advantages of MFCS are presented compared with single fuel cell stack. The scientific challenges and prospects for MFCS are suggested. The synergy between ICEs and MFCSs is the core idea to develop the MFCS. Abstract: To achieve carbon emission reduction and energy structure upgrading, the proton exchange membrane (PEM) multi-stack fuel cell system (MFCS) is an option to meet high-power demands in application scenarios. However, several barriers of the PEM MFCS have not been solved. This paper is aimed to summarize existing information and propose future R&D potentials. Firstly, detailed R&D activities and advances related to PEM MFCSs are reviewed including applications and design principle, architectures (fluidic, electrical, and thermal), power management strategy (PMS), water and thermal management, degraded mode operation, lifetime, efficiency, and hydrogen consumption. Among them, applications and design principle include application scenarios and influencing factors. Moreover, the architecture determination for MFCSs is the core issue, directly affecting the PMS, water and thermal management, degraded mode operation, lifetime, efficiency, and hydrogen consumption. It is noted that a MFCS is better than a single fuel cell system (SFCS) in fields of the lifetime, efficiency, and hydrogen consumption. Furthermore, the synergy between internal combustion engines (ICEs) and MFCSs is proposed to be applied for the MFCS R&D. Secondly, scientific challenges and prospects are presented, including effects of the load power-sharing on the lifetime and efficiency, comparisons of the performance, efficiency and lifetime, and control issues. Finally, the difference of several aspects is discussed, including the architecture, redundancy, lifetime, and PMS between a PEM MFCS and a PEM SFCS.